Role of Mango Mistletoe on Superoxide Dismutase (SOD) in Hypertensive Rats Exposed to DOCA-Salt - Suroyya, Mariyam; Sjakoer, Nour Athiroh Abdoes; Mubarakati, Nurul Jadid (JSMARTech, 2021)
Abstract: Hypertension is a condition where there is an abnormal rise in blood pressure that may be the primary cause of cardiovascular disease. Hypertension induces the production of free radicals known as reactive oxygen species (ROS) and oxidative stress. The purpose of this study is to further examine the function of Dendropthoe pentandra as an endogenous antioxidant modulator in this case superoxide dismutase (SOD)Â in hypertensive rats.The testing approach used is experimental. Data were analyzed using the one-way ANOVA test and the Post Hoc test to see variations in SOD levels in different treatments. This research used a hypertensive rat model induced by deoxycorticosterone acetate (DOCA) and salt. The number of animals tested was 25 white male rats divided into 5 groups, each containing 5 rats.The group consisted of a control group, a group of non- Extract methanolic of mango mistletoe hypertensive rats, and three groups of hypertensive rats receiving mango mistletoe methanolic extract (EMBM) at dosages of 50 mg/kg, 100 mg/kg, and 200 mg/kg body weight. Based on the results of the study, it is known that the levels of increased lung SOD with extract methanolic of mango mistletoe dosage variations in all treatment groups were not different. The administration of mango parasite methanolic extract at a dose of 50 mg / kgBW was optimum in increasing lung SOD levels in hypertensive rats.